ANALISIS KETERKAITAN PSAK NO. 22, PSAK NO. 65 KOMBINASI BISNIS TERHADAP PENYUSUNAN LAPORAN KEUANGAN KONSOLIDASI - Yahya, Rommist; Oktavianti, Glorya; Wahyu Andre, Bebi; Mayangsari, Sindi; Islamudin, Ardhi (Jurnal Ekonomi dan Manajemen, 2024)
Companies in today's modern era must understand PSAK and its implications to ensure proper and accurate consolidated financial statements based on applicable accounting standards. consolidated financial statements include information about the condition and financial position and results of operations of the parent company and one or more subsidiaries, as if they were a single company. The purpose of this study is to discuss the Financial Accounting Standards, namely PSAK No.22 and PSAK 65 in preparing consolidated financial statements. This research method uses a qualitative method with a descriptive or narrative approach obtained from library research. This article describes the relationship between PSAK No.22 and PSAK 65 regarding business combinations in an effort to prepare consolidated financial statements.